2021
DOI: 10.1111/jsap.13438
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of ultrasonography to detect hepatic and splenic lymphomatous infiltration in dogs and cats

Abstract: Objectives To determine the diagnostic accuracy of ultrasonography in the detection of lymphomatous infiltration of the liver and spleen in a population of dogs and cats with lymphoma. To determine if specific ultrasonographic features of the liver and spleen in dogs are associated with lymphomatous infiltration or a specific immunophenotype of multi‐centric lymphoma. Materials and Methods A blinded retrospective evaluation of ultrasonographic images of the liver and/or spleen in dogs and cats with cytological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Second, as this was a retrospective study, stage IV lymphoma was mainly classified based on the ultrasonographic appearance of hepatic and splenic involvement. While cytology or histopathology is the gold standard for diagnosing hepatic and splenic involvement in this disease, previous studies have shown that the ultrasonographic appearances of the spleen and liver, particularly a leopard-spotted splenic parenchyma, provide high specificity in detecting lymphomatous infiltration [ 51 , 52 ]. Third, all dogs were diagnosed with multicentric lymphoma based on cytological results, with most of them classified as having high-grade lymphoma according to the Kiel cytological classification.…”
Section: Limitationsmentioning
confidence: 99%
“…Second, as this was a retrospective study, stage IV lymphoma was mainly classified based on the ultrasonographic appearance of hepatic and splenic involvement. While cytology or histopathology is the gold standard for diagnosing hepatic and splenic involvement in this disease, previous studies have shown that the ultrasonographic appearances of the spleen and liver, particularly a leopard-spotted splenic parenchyma, provide high specificity in detecting lymphomatous infiltration [ 51 , 52 ]. Third, all dogs were diagnosed with multicentric lymphoma based on cytological results, with most of them classified as having high-grade lymphoma according to the Kiel cytological classification.…”
Section: Limitationsmentioning
confidence: 99%
“…18 The characteristics of the needles used to sample the spleen are not always specified in the literature, but when they are, multiple diameters are mentioned, ranging from 21 to 25-gauge (G), with 22G needles being predominant, presumably selected by routine or general opinion rather than scientific agreement. 13,17,[19][20][21][22][23] Based on 20 years of FNA experience and close collaboration with the cytopathology department, our team no longer uses 22G needles, which we consider to be painful and traumatic and lead to hemodiluted cytologic specimens. For FNA of the spleen and other organs, we have successfully used 23 and 25G needles for 15 years and recently introduced the use of 27G needles based on current practice in human medicine for thyroid puncture.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in human 16 and veterinary medicine 17 have suggested that US‐FN‐NA is more effective than US‐FNA as it gives specimens with similar cell morphology, higher cellularity, and less hemodilution 18 . The characteristics of the needles used to sample the spleen are not always specified in the literature, but when they are, multiple diameters are mentioned, ranging from 21 to 25‐gauge (G), with 22G needles being predominant, presumably selected by routine or general opinion rather than scientific agreement 13,17,19–23 …”
Section: Introductionmentioning
confidence: 99%